Portable capillary electrophoresis instrument with contactless conductivity detection for on-site analysis of small volumes of biological fluids - Greguš, Michal; Foret, František; Kubáň, Petr (Journal of chromatography. A, Including electrophoresis and other separation methods, 2016)
A novel, easy to use and portable capillary electrophoretic instrument for injection of small volumes of biological fluids equipped with contactless conductivity detection was constructed. The instrument is lightweight (<5 kg), all necessary parts including a tablet computer are accommodated in a plastic briefcase with dimensions 20 cm × 33 cm × 17 cm (w × l × h), allows hydrodynamic injection of small sample volumes and can continuously operate for at least 10 hours. The semi-automated hydrodynamic sample injection is accomplished via a specially designed PMMA interface that is able to repeatedly inject sample aliquots from a sample volume as low as 10 μL, with repeatability of peak areas below 5%. The developed interface and the instrument were optimized for the injection of biological fluids. Practical utility was demonstrated on the determination of formate in blood serum samples from acute methanol intoxication patients and on the analysis of ionic profile (nitrosative stress markers, including nitrite and nitrate) in the exhaled breath condensate from one single exhalation.
Keywords: Body Fluids; Humans; dusičnany; Nitrates; dusitany; Nitrites; Methanol; feces; formiáty; methanol; Breath Tests; Electrophoresis, Capillary; dechové testy; elektroforéza kapilární; lidé; Formates; Feces; tělesné tekutiny